The Effect of Deficit Irrigation on Grain Yield and Some Physiological Indicators of Sunflower (Helianthus annus L.) Cultivars - D Omidi Nasab; M Meskarbashee; A Rahnama Ghahfarokhi (پژوهشهای زراعی ایران, 2024)
IntroductionSunflower, one of the primary oilseed crops worldwide, is cultivated extensively due to its suitability for agricultural needs, high oil yield, and nutritional and medicinal value. However, drought remains the most critical limiting factor affecting sunflower productivity. In arid and semi-arid regions, the intensity of drought stress is predicted to increase in the future. Unfortunately, severe drought stress leads to significant reductions in both seed and oil production. While sunflower is moderately drought-tolerant, understanding the physiological and agronomic aspects of drought stress is crucial for sustainable management. Given that water, scarcity poses a significant threat to crop productivity and environmental resources are diminishing, effective irrigation management under water scarcity is becoming increasingly important. Materials and MethodsIn order to study the effects of deficit irrigation on grain yield and physiological traits of six sunflower cultivars, a field experiment was carried out in a split-plot arrangement based on randomized complete block design with three replications in 2019-2020 growing season. The experimental site was located in the research farm of the Safiabad Agricultural and Natural Resources Research and Education Center. Main plots consisted of three irrigation regimes including; control, moderate, and severe deficit irrigation (50, 70, and 90% of available moisture, respectively), and sub plots consisted of six sunflower cultivars including; Oscar, Felix, Shakira, Savana, Labad and Monaliza.Results and DiscussionDifferent levels of deficit irrigation differently caused a significant reduction in stomatal conductance, photosynthetic rate, chlorophyll index, relative water content, grain yield, grain number per head, grain weight per head, and oil yield, when compared to control. Oscar cultivar with the highest stomatal conductance, photosynthetic rate, and chlorophyll index, produced the highest economic oil and grain yield while the Shakira cultivar showed the lowest grain yield values in different levels of deficit irrigation. Oscar in 50% of field capacity and Shakira in 90% of field capacity showed the highest and lowest grain yield values (5.34 and 2.67 ton ha-1, respectively). Labad maintained the highest grain yield in 70 and 90% of field capacity relative to the control (4.41 and 4.28 ton ha-1, respectively). It seems that deficit irrigation leads to a significant reduction in grain yield by reducing the reproductive stage, producing fewer seeds, and the impossibility of transferring assimilates to fill the grains. Moreover, the reduction of oil percentage is probably due to the acceleration of achene ripening, giving the plant a chance to escape from drought, because carbohydrates first accumulate in the achenes and then turn into oil or any other substance. Photosynthetic rate, stomatal conductance, light absorption, relative water content, leaf area index, chlorophyll index, and transpiration rate decreased by 49, 25, 28, 26, 48, 22 and 78%, respectively in severe deficit irrigation, while water use efficiency and canopy temperature increased by 58 and 16 % respectively. ConclusionVarious levels of deficit irrigation exerted an influence on the physiological characteristics and grain yield of sunflower cultivars. The extent of water scarcity emerged as a significant factor shaping the cultivar responses to deficit irrigation. Felix and Labad exhibited higher oil yield and are thus recommended for cultivation in Dezful and analogous regions, owing to their superior grain yield and ability to sustain grain yield under deficit irrigation conditions.AcknowledgmentWe gratefully acknowledge funding support from Shahid Chamran University of Ahvaz project number SCU.AA1401.783..